2018
DOI: 10.1038/s41374-018-0073-0
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3/ASC-mediated alveolar macrophage pyroptosis enhances HMGB1 secretion in acute lung injury induced by cardiopulmonary bypass

Abstract: Our previous study showed that high levels of HMGB1 existed in rats following cardiopulmonary bypass (CPB)-induced acute lung injury (ALI) and neutralization of high-mobility group box 1(HMGB1) reduced CPB-induced ALI. However, the mechanism by which CPB increases HMGB1 secretion is unclear. Recent studies have shown that inflammasome-mediated cell pyroptosis promotes HMGB1 secretion. This study aimed to investigate the relationship between inflammasome-mediated pyroptosis and HMGB1 in CPB-related ALI. We empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 63 publications
2
84
1
Order By: Relevance
“…Further analysis by ELISA assay showed that MNs predepletion in conjunction with administration of aCALR additively suppressed the expression of pro-inflammatory cytokines, including TNF-alpha, IL-6 and IL-1beta in lung tissues ( Figure 6A) and BAL (Figure 6B). Cell pyroptosis is characterized with activation of NLRP3 inflammasome and release of both IL-1beta and IL-18 (39)(40)(41). Consistent with the results above, we observed moderately lower expression of IL-18 in the lung (Figure 6C, right panel) of aCALR-treated mice with or without MNs pre-depletion, indicating the suppressive effects of aCALR on macrophage pyroptosis independent of MNs.…”
Section: Acalr Suppressed Ali Independent Of Circulating Monocytes Ansupporting
confidence: 90%
See 2 more Smart Citations
“…Further analysis by ELISA assay showed that MNs predepletion in conjunction with administration of aCALR additively suppressed the expression of pro-inflammatory cytokines, including TNF-alpha, IL-6 and IL-1beta in lung tissues ( Figure 6A) and BAL (Figure 6B). Cell pyroptosis is characterized with activation of NLRP3 inflammasome and release of both IL-1beta and IL-18 (39)(40)(41). Consistent with the results above, we observed moderately lower expression of IL-18 in the lung (Figure 6C, right panel) of aCALR-treated mice with or without MNs pre-depletion, indicating the suppressive effects of aCALR on macrophage pyroptosis independent of MNs.…”
Section: Acalr Suppressed Ali Independent Of Circulating Monocytes Ansupporting
confidence: 90%
“…NLRP3 is a key component of NLRP3 inflammasome during cell pyroptosis, contributing to the uncontrolled lung inflammation in ARDS/ALI (39,41). However, it remains unknown whether macrophage pyroptosis is involved in the immune suppressive effects of aCALR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chang and colleagues demonstrated that LPC induces cytotoxicity/apoptosis and IL-8 production in human endothelial cells via mechanisms dependent on ROS, ATM/Chk2, ATR/Chk2, and PI3K/Akt signaling (67). Pyroptosis is a form of proinflammatory cell death and (68) can be mediated by inflammasome-dependent caspase-1 activation (69) or caspase-11 (70), which is responsible for the cleavage and/or maturation of gasdermin D (GSDMD) and membrane pore formation (71), IL-1β (72), IL-18 (73), HMGB1 (74), and LDH release (75). Pyroptosis has been shown to play important roles in cardiovascular diseases, such as atherosclerosis (76).…”
Section: Discussionmentioning
confidence: 99%
“…A cardiopulmonary bypass machine is used in this surgery to circulate oxygenated blood through body during the operation. 32 For removing carbon dioxide used a machine that is pumped blood out of heat and then the machine is filled with oxygen. The oxygenated blood is pumped back into body without going through the heart and lungs.…”
Section: Bypass Surgerymentioning
confidence: 99%